TRANSFORMATIONAL LEADERSHIP IN PRIVATE HIGHER EDUCATION: A QUALITATIVE STUDY ON FACULTY ENGAGEMENT AND INSTITUTIONAL PERFORMANCE AT SOUTHEAST SULAWESI - Qadri, Muhammad Nuzul; Asraf, Asraf; Rahmah, Wahyuni; Bagea, Arfin (Management Studies and Business Journal (PRODUCTIVITY), 2025)
Transformational leadership is recognized as one of the most effective leadership styles in the context of higher education, especially in improving lecturer engagement and institutional performance. In Southeast Sulawesi, the challenges faced by private universities in implementing this leadership are a major concern, given the importance of the role of lecturers in achieving academic goals. This study identifies a knowledge gap related to the lack of understanding of transformational leadership that can hinder the development of higher education institutions. The methodology used in this study is a descriptive qualitative approach, with in-depth interviews with relevant informants in private universities. The findings of this study provide significant implications for the development of leadership theory and practice, as well as offering solutions for institutional leaders in implementing more effective leadership styles to improve the quality of education. This study is expected to be a reference for further studies on transformational leadership in the context of higher education, as well as providing new insights for the development of better management strategies.